Sistemi di immagini, sistemi di oggetti - Monica Baggio (Cahiers Mondes Anciens)
The figurative system of Apulian vases dating back to the second half of the fourth century B.C., specifically the Baltimore Painter’s vases, constitutes a privileged observatory to shed new light on the mechanisms of feminine representation.